How are smallholder farmers coping with and adapting to climate-related shocks in Kaffrine Climate-Smart Village, Senegal? - Bonilla Findji, Osana; Ortega, Angelly; Ouédraogo, Mathieu; Fall, Mamadou; Chabi, Adéyèmi; Eitzinger, Anton; Zougmoré, Robert B.; Läderach, Peter R.D. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This synthesis presents an analysis of the results from the 2019 implementation of the Climate-Smart Agriculture (CSA) Monitoring framework in Kaffrine (Senegal). This work contributes to the Activity 2.2 ‘Mainstreaming of evidence-based CSA options within the selected value chains’, in the context of the CCAFS-EU-IFAD grant reference 2000002575 for the research project “Building livelihoods and resilience to climate change in East & West Africa: Agricultural Research for Development (AR4D) for large-scale implementation of Climate-Smart Agriculture” led by the Alliance of Bioversity International and CIAT.